2015
DOI: 10.1186/s12886-015-0160-6
|View full text |Cite
|
Sign up to set email alerts
|

A Population-based survey of the prevalence and types of glaucoma in Nigeria: results from the Nigeria National Blindness and Visual Impairment Survey

Abstract: BackgroundGlaucoma is the leading cause of irreversible blindness worldwide. There tends to be a lower reporting of glaucoma in Africa compared to other blinding conditions in global burden data. Research findings of glaucoma in Nigeria will significantly increase our understanding of glaucoma in Nigeria, in people of the West African diaspora and similar population groups. We determined the prevalence and types of glaucoma in Nigeria from the Nigeria National Blindness and Visual Impairment cross-sectional Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
80
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 55 publications
13
80
4
1
Order By: Relevance
“…The Baltimore Eye Survey (9) found that the relative risk of having glaucoma is increased 3.7-fold for individual who have a sibling with primary open-angle glaucoma compared to an individual who has a parent with primary open angle glaucoma that has a 2.2-fold risk of developing glaucoma. It is obvious from our study like the other studies (5,14,20) that the prevalence of primary open-angle glaucoma is higher amongst first degree relatives than the general populations (2,4,7,8,10) . Therefore, every effort should be directed at getting this high-risk population screened for the disease.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The Baltimore Eye Survey (9) found that the relative risk of having glaucoma is increased 3.7-fold for individual who have a sibling with primary open-angle glaucoma compared to an individual who has a parent with primary open angle glaucoma that has a 2.2-fold risk of developing glaucoma. It is obvious from our study like the other studies (5,14,20) that the prevalence of primary open-angle glaucoma is higher amongst first degree relatives than the general populations (2,4,7,8,10) . Therefore, every effort should be directed at getting this high-risk population screened for the disease.…”
Section: Discussionsupporting
confidence: 60%
“…The Nigeria Blindness Survey has shown that most of the over 1.2 million adults with glaucoma are not aware that they have the disease (3,4) . It is critical to note that symptoms occur late in Primary open angle glaucoma (POAG).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The glaucoma-defining VCDR values for the 97.5 th (0.7) and 99.5 th (0.75) percentiles in the study population 5 were applied, reporting a glaucoma prevalence of 5.02% (95%CI 4.60-5.47) among adults aged 40-years old and above. 6 The i-VCDR grading by Moorfields Eye Hospital…”
Section: Introductionmentioning
confidence: 99%